Type I interferon receptor signaling delays Kupffer cell replenishment during acute fulminant viral hepatitis - Borst, Katharina; Frenz, Theresa; Spanier, Julia; Tegtmeyer, Pia-Katharina; Chhatbar, Chintan; Skerra, Jennifer; Ghita, Luca; Namineni, Sukumar; Lienenklaus, Stefan; Köster, Mario; Heikenwaelder, Mathias; Sutter, Gerd; et al. (Journal of hepatology, 2018)
[Display omitted] •During acute viral hepatitis local IFN-I responses modulate liver inflammation.•IFNAR triggering of Kupffer cells protects against liver pathology during acute viral hepatitis.•Acute viral hepatitis induces Kupffer cell loss independently of direct infection.•Hepatitis-induced Kupffer cell loss is reversed by infiltrating blood monocytes.•In acute viral hepatitis IFNAR triggering of monocytes delays replenishment of monocyte-derived Kupffer cells. Virus-induced fulminant hepatitis is a major cause of acute liver failure. During acute viral hepatitis the impact of type I interferon (IFN-I) on myeloid cells, including liver-resident Kupffer cells (KC), is only partially understood. Herein, we dissected the impact of locally induced IFN-I responses on myeloid cell function and hepatocytes during acute liver inflammation. Two different DNA-encoded viruses, vaccinia virus (VACV) and murine cytomegalovirus (MCMV), were studied. In vivo imaging was applied to visualize local IFN-β induction and IFN-I receptor (IFNAR) triggering in VACV-infected reporter mice. Furthermore, mice with a cell type-selective IFNAR ablation were analyzed to dissect the role of IFNAR signaling in myeloid cells and hepatocytes. Experiments with Cx3cr1+/gfp mice revealed the origin of reconstituted KC. Finally, mixed bone marrow chimeric mice were studied to specifically analyze the effect of IFNAR triggering on liver infiltrating monocytes. VACV infection induced local IFN-β responses, which lead to IFNAR signaling primarily within the liver. IFNAR triggering was needed to control the infection and prevent fulminant hepatitis. The severity of liver inflammation was independent of IFNAR triggering of hepatocytes, whereas IFNAR triggering of myeloid cells protected from excessive inflammation. Upon VACV or MCMV infection KC disappeared, whereas infiltrating monocytes differentiated to KC afterwards. During IFNAR triggering such replenished monocyte-derived KC comprised more IFNAR-deficient than -competent cells in mixed bone marrow chimeric mice, whereas after the decline of IFNAR triggering both subsets showed an even distribution. Upon VACV infection IFNAR triggering of myeloid cells, but not of hepatocytes, critically modulates acute viral hepatitis. During infection with DNA-encoded viruses IFNAR triggering of liver-infiltrating blood monocytes delays the development of monocyte-derived KC, pointing towards new therapeutic strategies for acute viral hepatitis. Viral infection can cause fulminant hepatitis, which in turn is a major cause of acute liver failure. Herein, we aimed to study the role of type 1 interferon responses in acute viral hepatitis. We identified that during infection with DNA-encoded viruses, type 1 interferon receptor triggering of blood monocytes delays the development of monocyte-derived Kupffer cells. This points to new therapeutic strategies for acute viral hepatitis.